A comparative study of the incidence of sore throat with the laryngeal mask airway. - John Dingley (Anaesthesia, 1994)
In a prospective study of 150 patients randomly assigned to three groups, we have compared the incidence and duration of sore throat after a standard anaesthetic regimen using three different methods of airway management: facemask; laryngeal mask, and laryngeal mask with insertion aid. The insertion aid is currently being developed by Portex Ltd and is intended both to facilitate accurate placement of the laryngeal mask and to reduce trauma during insertion. All the patients were women undergoing short operative procedures requiring minimal postoperative analgesia. The incidence of sore throat was significantly less with a facemask (8%) than with the laryngeal mask when used without the insertion aid (28.5%) (p < 0.02). When using the insertion aid the incidence was 18% and this was not statistically different from the facemask. The presence of blood on the laryngeal mask (22%) was less likely when the insertion aid was used (4%) (p < 0.02).